Implantasi Lensa Intraokular Retropupilar Tipe Iris Claw pada Pasien dengan Dislokasi Lensa Intraokular Tahap Lanjut – Laporan Kasus: Laporan Kasus - Ly, Elsye Jasicha; Faizal, Alif Reza (Cermin Dunia Kedokteran, 2026)
Introduction: Late intraocular lens dislocation is an uncommon complication of cataract surgery but still a serious condition. Surgical approaches to improve better vision is by repositioning the existing intraocular lens (IOL) or replacing with a new IOL by fixing it either to anterior chamber (ACIOL), to the scleral wall, or to the iris (iris claw). Case: A 53-year-old woman with blurry vision in the past 2 years with history of phacoemulsification cataract surgery on both eyes in 2008. The examination showed the patient's left eye had 20/400 vision with a posterior dislocated IOL in the anterior vitreous cavity within the pupillary area. Considering the possibility of subclinical damage from previous cataract surgery, the low Endothelial Cell Density and approximately 15% ruptured ciliary zonule, retropupillary iris claw was chosen as the surgical approach. The visual acuity improved to 20/40 at follow up one week later, and improved to 20/30 after one month, iris claw intraocular lens (ICIOL) was intact with no complications. Discussion: Late IOL dislocation is a rare but increasingly recognized late complication of cataract surgery, primarily resulting from progressive zonular weakness, with aging likely contributing in this patient. Successful management was achieved by exchanging the dislocated IOL with a retropupillary iris claw IOL, providing good visual recovery without major early postoperative complications. Conclusion: Replacing new IOL using retropupillary iris claw procedure as a less invasive and safe procedure can improve visual acuity with minimal complication.